Digital Marketing Strategy Brand Awareness in Increasing Sales in the Fashion Industry Based on Online Data - Syerin Tiara Fatrecia; Veta Lidya Delimah Pasaribu (Indonesian Journal of Accounting and Financial Technology, 2025)
This study discusses the role of digital marketing strategies in enhancing brand awareness and sales in the online fashion industry. Through a literature review, it was found that the use of social media, creative visual content, influencer marketing, and omnichannel integration significantly contributes to building brand awareness, increasing consumer engagement, and driving customer loyalty and purchase intention. The synergy between technology and marketing enables rapid adaptation to market changes. The study recommends continued investment in innovative digital tools and consistent brand identity as key factors for sustainable growth in the online fashion market.